Edmund Randerath (1899-1961): experimental proof for the glomerular origin of proteinuria - Waldherr, Rüdiger; Ritz, Eberhard (Kidney international, 1999)
Edmund Randerath (1899-1961): Experimental proof for the glomerular origin of proteinuria. A century ago, Edmund Randerath (1899-1961), who was one of the pioneers in nephrology that provided indirect experimental proof for the glomerular origin of proteinuria, was born. In the first decades of this century, the concept prevailed that “nephrosis” was a process of primary tubular cell degeneration. In contrast to prevailing opinion, he interpreted these changes to be the result of the uptake and storage of serum proteins after they had been filtered in the glomerulus. Edmund Randerath proved the glomerular origin of proteinuria by astute experiments in amphibia. In the salamander, an intraperitoneal injection of albumin provoked the supposedly “degenerative” changes of tubular epithelial cells in only those nephrons that drained the coelomic cavity and were devoid of glomeruli, but not in those nephrons that were closed and attached to glomeruli. This observation provided incontrovertible evidence that the presence of serum proteins in tubular fluid was a prerequisite for the development of the tubular epithelial cell changes typically seen in nephrotic patients.